A Psychophysical Protocol to Develop Ergonomic Recommendations for Sitting and Standing Workstations. (June 2016) - Lin, Michael Y.; Catalano, Paul; Dennerlein, Jack T.
Objective: The aim of this study was to determine user self-selected setup for both sitting and standing computer workstations and identify major differences. Background: No current ergonomic setup guideline for standing computer workstations is available. Methods: Twenty adult participants completed four 45-min sessions of simulated office computer work with an adjustable sit-stand computer workstation. Placement and relative position of all workstation components, including a cordless mouse, a cordless keyboard, a height-adjustable desk, and a 22-inch monitor mounted on a mechanical-assisted arm were recorded during the four sessions, which alternated between sitting and standing for each session. Participants were interrupted four times within each session, and the workstation was "reset" to extreme locations. Participants were instructed to adjust the location to achieve the most comfortable arrangement and to make as many adjustments during the session to achieve this goal. Results: Overall, users placed the keyboard closer to their body (sternum), set desk height lower than their elbow, and set the monitor lower relative to their eyes with a greater upward tilt while standing compared to sitting. During the 45-min sessions, the number of adjustments participants made became smaller and over the four sessions was consistent, suggesting the psychophysical protocol was effective and consistent. Conclusion: Users preferred different workstation setups for sitting and standing computer workstations. Therefore, future setup guidelines and principles for standing computer workstations may not be simply translated from those for sitting. Application: These results can serve as the first step toward making recommendations to establish ergonomic guidelines for standing computer workstation arrangement.